2013
DOI: 10.1093/jac/dkt047
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and genetic diversity of methicillin-resistant Staphylococcus aureus carried by humans and animals across livestock production sectors

Abstract: This systematic cross-sector survey revealed a high prevalence of multiresistant livestock-associated MRSA on Belgian veal calf farms as compared with other farm types. MRSA harbouring mecC was detected at a low frequency in beef and dairy cows, but not in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 27 publications
4
59
1
1
Order By: Relevance
“…In this study two CC398 isolates were found to be susceptible to tetracycline while tetracycline susceptible strains are only very rarely found in CC398 MRSA [46]. The prevalence of erythromycin, clindamycin, kanamycin and gentamicin resistance in this collection is extremely high compared to what has been found in strains from other origins in Belgium [14,34]. The isolate with the lowest level of multi-resistance was resistant to two additional antimicrobials.…”
Section: Discussionmentioning
confidence: 84%
“…In this study two CC398 isolates were found to be susceptible to tetracycline while tetracycline susceptible strains are only very rarely found in CC398 MRSA [46]. The prevalence of erythromycin, clindamycin, kanamycin and gentamicin resistance in this collection is extremely high compared to what has been found in strains from other origins in Belgium [14,34]. The isolate with the lowest level of multi-resistance was resistant to two additional antimicrobials.…”
Section: Discussionmentioning
confidence: 84%
“…CC599-MRSA-XI have previously been detected in cattle [159] and in a domestic cat [160]. To the best of our knowledge, there are no descriptions of CC599-MRSA-XI in wildlife, and to date no reports of CC599-MSSA at all.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these differences may be accounted for by the presence of vga genes -as vga(A) and vga(C) confer resistance to the lincosamide clindamycin, quinupristin/dalfopristin and tiamulin but not to the macrolide erythromycin (Kadlec et al, 2010) -and either inducible or constitutively expressed erm genes, which, respectively, confer resistance to erythromycin or to both erythromycin and clindamycin (Livermore et al, 2001). Erm genes were frequently detected in bovine MRSA CC398 isolates in a recent Belgian study (Vandendriessche et al, 2013).…”
Section: Multiple-resistance Patterns In Meticillin-resistant Staphylmentioning
confidence: 99%